Metabolic pathway prediction of core microbiome based on enterotype and orotype - Lee, Song Hee; Lee, Han; You, Hee Sang; Sung, Ho-joong; Hyun, Sung Hee (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Identification of key microbiome components has been suggested to help address the maintenance of oral and intestinal health in humans. The core microbiome is similar in all individuals, whereas the diverse microbiome varies across individuals, based on their unique lifestyles and phenotypic and genotypic determinants. In this study, we aimed to predict the metabolism of core microorganisms in the gut and oral environment based on enterotyping and orotyping. Materials and methods Gut and oral samples were collected from 83 Korean women aged 50 years or older. The extracted DNA was subjected to next-generation sequencing analysis of 16S rRNA hypervariable regions V3–V4. Results Gut bacteria were clustered into three enterotypes, while oral bacteria were clustered into three orotypes. Sixty-three of the core microbiome between the gut and oral population were correlated, and different metabolic pathways were predicted for each type. Eubacterium_g11, Actinomyces, Atopobium, and Enterococcus were significantly positively correlated between the gut and oral abundance. The four bacteria were classified as type 3 in orotype and type 2 in enterotype. Conclusion Overall, the study suggested that collapsing the human body’s multidimensional microbiome into a few categories may help characterize the microbiomes better and address health issues more deeply.